Effects of trypanosomosis on some blood biochemical parameters in rabbits (1999)
The effect of trypanosomosis on blood biochemical Parameters were studied in 20 New Zealand white rabbits of 6 to 7 months of age. Mean total protein and globulin levels in the infected rose significantly (P<0.05) while the mean albumin level decline in the same group simultaneously. Mean total plasma Cholesterol, trlglyceride concentration mean glutamate oxaloacelate transaminase (GOT) and the glutamate pyruvate transaminase (GPT) levels decreased significantly (P<0.05) in the infection group. The implications of these results are briefly discussed